Relevance of the Values of Bedhaya Ketawang In the Life of Society Today - Maryono Maryono; Setya Widawati; Ni Nyoman Yuliarmaheni; Slamet MD; Dwi Wahyudiarto; Midiyanto Midiyanto (Gelar : Jurnal Seni Budaya, 2022)
Surakarta, a city formerly under the rule of the New Mataram dynasty established by Paku Buwana II in 1746, inherited a wealth of arts which led to its designation as a cultural center. Jumenengan is a cultural legacy in the form of a ceremony, held annually in the Javanese month of Ruwah, on the day of Selasa Kliwon, or Anggara Kasih, to celebrate the anniversary of the coronation of the king of Kasunanan Surakarta. The main prerequisite of the Jumenengan ceremony is the performance of the Bedhaya Ketawang dance, which provides legitimacy for the ceremony. The position of the Bedhaya Ketawang dance in the Jumenengan ceremony is as an heirloom with magical, sacred, prestigious value. Its presence gives legitimacy and credibility to the continued power of the king. As a cultural legacy, the Bedhaya Ketawang dance contains life values that can be absorbed both implicitly and explicitly. These include spiritual values, values of love for the natural environment, ethical values, aesthetic values, and values of love, all of which are relevant to the life of society today. The relevance of these values provides encouragement and motivation to build and develop the character of the Indonesian nation today as a society of faith, devotion to God, noble character, healthy knowledge, skill, creativity, independence, democracy, and responsibility.